PENGOPTIMALAN LIMA ASPEK PERKEMBANGAN ANAK MELALUI PENGEMBANGAN LANJUT ALAT PERMAINAN EDUKATIF ULAR TANGGA - Prilya Shanty Andrianie; Yustinus Joko Dwi Nugroho (Program Studi S1 Psikologi, 2019)
This study is entitled Optimizing the Five Aspects of Child Development Through the Advanced Development of the Educational Instrument of Snakes and Ladders which is a follow-up study in the previous year (multi years). The research method used is Research and Development (R&D), which is a research method used to produce certain products and test the effectiveness of these products (Sugiyono, 2012). Validation of measurement tools and modules is done in two ways, namely: Focus Group Discussion (FGD) and module validation (content validity) is done by Professional Judgment. Based on the results of the study it can be concluded that the preparation of the Ladder Snake APE can be said to be valid to stimulate five aspects of child development with the results of 40% validator stating that the APE is suitable for stimulating five aspects of child development, and 60% states that the APE is very suitable for stimulating the five aspects of child development. While for the preparation of the APE Snake Ladder Module, it can also be said to be valid with the results of the 67% assessment of the validator stating that the module is very suitable and 33% of the validator stating that the module is appropriate. The output produced in this study is in the form of APE Snakes and Ladders products to stimulate five aspects of child development, the use of APE modules, and the National Journal of ISSN.